EMC assassement criteria and interference protection for basic radio services in accordance with ITU-R recommendations - Stancheva, Anushka (Yearbook Telecommunications, 2021)
The effect of unwanted energy due to one or a combination of several desired and unwanted emissions upon reception in a radio communication system results in performance degradation, misinterpretation or loss of information. Multiple sources of interference may affect the receiver input: services of the same type or other operating in the same frequency band, services operating in adjacent frequency bands, sources generating continuous or short term interferences, fixed or mobile sources, etc. To prevent such interfering situations, a key element is the standardization of appropriate criteria for electromagnetic compatibility (EMC) and interference protection (IPC). The purpose of the studies and analyzes in this article is to systematize the criteria for electromagnetic compatibility for basic radio services based on the Publications of ITU-R. Criteria for four important areas of radio communications covering fixed, fixed satellite, broadcasting and mobile radio services are compared. Contributions are the categorization of the criteria according to the type of interfering signal and the results of the analyses, which show that the regulatory requirements and practical methods for interference protection and EMC for different radio services differ. Detailed criteria for predicting the probability of interference being standardized only for some radio services.